A Solving Method for Forward Kinematics of 3-PRS Parallel Mechanism - Junjie Huang; Bowei Hu; Jindian Song (Jixie chuandong)
It is necessary that parallel mechanisms are researched because of the complex and multiple kinematics solution, and it is the research hotspot and the difficulty. The method of combining D-H and graphical visualization is put forward to solve the forward kinematics of 3-PRS parallel mechanism. Firstly, the spherical hinge in parallel mechanisms is equivalent converted, and then the kinematics analysis is carried out by D-H method, the forward kinematics equation is deduced. Secondly, the 16 forward solutions are obtained by iterative method. The 16 visible graphics are intuitively obtained by visual programming, that is, the forward kinematics solution of the parallel mechanism is obtained. In the end, the result shows that one of the obtained graphics is coincident with the actual position and pose for 3-PRS parallel mechanism. This method is valid and correct, and it is also suitable for solving forward kinematics of other types of parallel mechanism.